Impact of COPD or Asthma on the Risk of Atrial Fibrillation: A Systematic Review and Meta-Analysis - Xue, Zhengbiao; Guo, Siyu; Liu, Xiao; Ma, Jianyong; Zhu, Wengen; Zhou, Yue; Liu, Fuwei; Luo, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background: Respiratory diseases related to chronic pulmonary ventilation dysfunction are mainly composed of chronic obstructive pulmonary disease (COPD) and asthma. Our meta-analysis aimed to illustrate the association of COPD or asthma with risk of atrial fibrillation (AF). Methods: We systematically searched the databases of the PubMed, Embase, and Cochrane library until December 2021 for studies focusing on the relationship between COPD or asthma and AF risk. Due to the potential heterogeneity across studies, the random-effects model was used to pool the studies. Results: Our meta-analysis included 14 studies. Based on the random-effects model, the pooled analysis showed that COPD (risk ratio[RR]=1.74, 95% confidence interval [CI]: 1.70-1.79) and asthma (RR=1.08, 95% CI: 1.04-1.12) were significantly associated with an increased risk of AF. The results did not change after each study was excluded. Conclusion: Our current data suggested that COPD or asthma with associated with an increased risk of AF.